Rehabilitation of Ectodermal Dysplasia Using CAD/CAM Mandibular Complete Denture and Maxillary Overdenture: A Clinical Report - Hatem Alqarni; Faisal Alzeghaibi; Sahar Alotaibi; Raghad Alamri; Raghad Aljohani; Majed S. Altoman; Mohammed A. Alfaifi (Case Reports in Dentistry)
Ectodermal dysplasia is a genetic disorder characterized by the abnormal development of two or more ectodermally driven structures, leading to various clinical manifestations such as sparse hair, dry skin, and hypodontia or anodontia. The absence of teeth significantly impacts the quality of life for individuals affected by this condition. This article presents a clinical case report of a patient with ectodermal dysplasia who underwent full mouth rehabilitation using computer-aided design/computer-aided manufacturing (CAD/CAM) technology to fabricate a mandibular complete denture and a maxillary overdenture.